Prevention and the limits of the criminal law - Ashworth, Andrew; Zedner, Lucia; Tomlin, Patrick, 1981- (Oxford : Oxford University Press, 2013)
Are preventive justice measures justified? Do they needlessly blur the boundaries between criminal and civil law, signalling a change in the architecture of security? The contributors in this volume re-assess the foundations for the range of coercive measures that states now take in the name of prevention and public protection.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Preventive law; Criminal law -- Philosophy